Tourist Shopping Trends: A Bibliometric Study of Influential Literature and Leading Scholars (1957-2024) - Sulistyowati, Tussi; Nisak, Solihatun; Mujanah, Siti; Halik, Abdul (Pancasila International Journal of Applied Social Science, 2025)
This research employed bibliometric analysis to explore the evolving interest in tourist shopping and its influence on tourist behaviour. It utilized Publish or Perish software to examine publication, author, and journal communication patterns within the Scopus database. An initial keyword search for "tourist shopping" documents yielded 744 entries, refined to 664 after removing erratum, retracted items, authorless entries, and duplicates from 1957 to 2024. The findings revealed significant trends in research output, notably a gradual increase in publications from 1979 onward, culminating in a peak of 56 papers in 2021, coinciding with studies on the impacts of COVID-19 on tourism shopping. The analysis highlighted influential works, including Friedberg's book, which received 591 citations, and identified vital journals and authors in the field, with Tourism Management leading in productivity. Eight distinct research clusters were revealed, emphasizing community connections, consumer motivations, and international shopping behaviours. Overall, the study illustrates a rich tapestry of scholarly work dedicated to understanding the complexities of tourist shopping, consumer behaviour, and marketing strategies, providing valuable insights for future research directions.